Respuesta :
For this case we have that by definition:
[tex]cosine (a-b) = Cosine (a) * cosine (b) + sine (a) * sine (b)[/tex]
If we want to solve [tex]cosine (270-theta)[/tex]then:
[tex]cosine (270-theta) =\\cosine (270) * cosine (theta) + sine (270) * sine (theta) =[/tex]
We know that:
[tex]cosine (270) = 0\\sine (270) = - 1[/tex]
Substituting:
[tex]cosine (270) * cosine (theta) + sine (270) * sine (theta) =\\0 + (- 1 * sine (theta)) =\\-sine (theta)[/tex]
Answer:
[tex]cosine (a-b) = Cosine (a) * cosine (b) + sine (a) * sine (b)[/tex]